Agribusiness higher education development – training needs analysis - Juracak, Josip; Kárpáti, László (Applied Studies in Agribusiness and Commerce, 2008)
With the tremendous changes in political and economic systems of the Republic of Croatia after independence, new challenges have been put to the higher education system as well. The system used to be structured to serve a centrally planed economy with predominantly state ownership. Universities were producing graduates to be employed on statefarms,inagri-foodsystems(socalled„kombinats“),the state owned processing industry or cooperatives. The graduates were specialised in particular branches, such as crop production, vegetable production or livestock husbandry. Therefore, they were not educated to understand the whole system of a company or the agri-food system. In one word, they were not prepared to run firms as managers, although they were highly educated. Small and medium size entrepreneurs in agri-food business have been rather an exception than a rule, and prior to the transition there was not to much experience in managing, financing or marketing for such a firms.